Different adiposity indices and their association with blood pressure and hypertension in middle-aged urban black South African men and women: findings from the AWI-GEN South African Soweto Site - Pedro T. Pisa; Lisa K. Micklesfield; Juliana Kagura; Michele Ramsay; Nigel J. Crowther; Shane A. Norris (BMC, 2018)
Abstract Background To report associations between different adiposity indices [anthropometric and dual-energy X-ray absorptiometry (DXA) measures] and blood pressure (BP) and hypertension in urban black South African adults. Methods Anthropometric and DXA whole body measures were performed on 1026 men and 982 women. Participants were classified as being hypertensive if they had a systolic BP (SBP) ≥ 140 mmHg and/or diastolic (DBP) ≥ 90 mmHg. Within each gender the relationship of adiposity with BP and hypertension risk was assessed using linear and logistic regression models respectively. Bivariate models were computed for each body composition variable. Furthermore, we computed a multiple regression model to illustrates how body composition parameters are associated with the outcome variables independent of each other. Results The males were significantly taller and had a higher fat free soft tissue mass (FFSTM), DBP and socio-economic status, and were more likely to use tobacco and be hypertensive (48.0% vs. 38.8%). The females had higher body mass index (BMI), waist circumference (WC), fat mass (FM), subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), FM/FFSTM ratio and body fat % than males. All body composition parameters were positively associated with hypertension. In both males and females, the FM/FFSTM ratio associated the strongest with hypertension illustrating the following odds ratios [males: 70.37 (18.47, 268.16) p ≤ 0.001; females 2.48 (0.86,7.21) p = 0.09]. The multiple regression model, indicated that the VAT and WC significantly associated with both SBP and DBP in the men and women respectively, whilst WC was the only significant predictor for hypertension. Conclusions All body composition parameters were associated with hypertension and FM/FFSTM ratio showed the strongest relationship. It was reassuring that WC remains a useful measure of central adiposity that can be used as a risk indicator for hypertension if more sophisticated measures are not available. Furthermore, our data in part, implies that reducing abdominal adiposity in aging adults could contribute to reducing the risk of elevated blood pressure and hypertension.